Fluctuation of depressive symptoms in cognitively unimpaired participants and the risk of mild cognitive impairment 5 years later: Results of the Heinz Nixdorf Recall study - Jokisch, Martha; Schramm, Sara; Weimar, Christian; Moebus, Susanne; Gronewold, Janine; Dragano, Nico; Jöckel, Karl-Heinz (Frontiers in Behavioral Neuroscience, 2022)
Background: Depression might be an independent risk factor for cognitive decline, a prodromal dementia symptom or a reaction to cognitive/functional impairment. Objective: To investigate the association between (1) depressive symptoms and (2) depressive symptom patterns over 13 years with incident mild cognitive impairment (MCI) five years later. Methods: We included 724/823 cognitively unimpaired men/women who participated in the population-based Heinz Nixdorf Recall study (t1: 2005-2008, ø62.9 years; t2: 2010-2015, ø68.1 years). Depressive symptoms were assessed in the study center and during six postal follow-ups using the short form of the Center for Epidemiologic Studies Depression Scale (CES-D). Relative risks (RR; 95% confidence intervals) for MCI at t2 (men/women: 71/76) were estimated for CES-D at t1 (linear and dichotomized at ≥17, cut-off for clinically relevant depressive symptoms) and CES-D fluctuations over 13 years (stable low, large fluctuations, stable high/stable around cut-off) using log-linear regression models with Poisson working likelihood adjusted for age, sex, education, diabetes mellitus, coronary heart disease and stroke. Results: Fully adjusted risk for MCI at t2 (per CES-D point increase at t1) was elevated for the total cohort, (1.053, 1.031-1.076), men (1.046, 1.012-1.081) and women (1.059, 1.029-1.090). Applying the dichotomized CES-D, risk for MCI was substantially increased for the total cohort (2.22 (1.38-3.58)) and in women (2.59 (1.46-4.58). Large CES-D fluctuations and stable high/stable around cut-off were associated with increased RR for MCI in the total cohort and in women compared to stable low symptoms. Conclusion: Depressive symptoms predicted MCI in cognitively unimpaired participants of our population-based study. Adequate treatment of depression may therefore contribute to the maintenance of normal cognition and delay dementia onset.